2022
DOI: 10.1186/s40729-022-00402-w
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year prospective randomized clinical trial of alveolar bone crest response and clinical parameters through 1, 2, and 3 years of clinical function of implants placed 4 months after alveolar ridge preservation using two different allogeneic bone-grafting materials

Abstract: Purpose The aim of this study was to longitudinally evaluate changes in alveolar bone crest (ABC) levels and differences in resorption rates (RR) between the tested grafting materials following alveolar ridge preservation (ARP) after tooth extraction after 1, 2, and 3 years (T1–T8) of clinical function. Methods Patients were randomly assigned to two different bone allografts (group 1 maxgraft®, group 2 Puros®) for ARP. Non-restorable teeth were mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
3
6
0
Order By: Relevance
“…Group C of both materials demonstrated a comparable delayed wound healing and group C of test group 1 (Maxgraft®) demonstrated a higher amount of bone resorption which made a second bone grafting procedure at time of implant placement necessary. This difference in bone resorption was also observed in another recently published prospective randomized clinical trial [ 63 ]. Again, there was no statistically significant difference detectable between both materials, which was most likely due to the low sample size, but a strong clinical association was observed.…”
Section: Discussionsupporting
confidence: 80%
“…Group C of both materials demonstrated a comparable delayed wound healing and group C of test group 1 (Maxgraft®) demonstrated a higher amount of bone resorption which made a second bone grafting procedure at time of implant placement necessary. This difference in bone resorption was also observed in another recently published prospective randomized clinical trial [ 63 ]. Again, there was no statistically significant difference detectable between both materials, which was most likely due to the low sample size, but a strong clinical association was observed.…”
Section: Discussionsupporting
confidence: 80%
“… Bone resorption rates: a 3-year prospective randomized clinical trial aimed to analyze the changes in alveolar bone crest levels and differences in resorption rates between various grafting materials used in ARP post-tooth extraction. The study spanned evaluations over 1, 2, and 3 years of clinical function [ 44 ]. Another study observed that alveolar ridge resorption often occurs within the first 6 months post-tooth extraction, with the resorption rate decreasing gradually over the years.…”
Section: Main Textmentioning
confidence: 99%
“…Implant treatments in affected patients may require preceding or simultaneous boneaugmentative procedures [2]. Among the different treatment options, block grafts have recently attracted considerable interest due to their ability to predictably increase the horizontal alveolar dimension [3][4][5][6]. Recent systematic reviews and individual studies have reported the superior capacity to maintain volume and reduced risk of graft dislocation of block grafting compared to guided bone regeneration (GBR) using particulate material [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The material undergoes physical and chemical purification steps, including solvent extraction and oxidative chemical treatment, followed by freeze-drying and sterilization to remove cells and antigens, inactivate potential viruses and bacteria, and render the material sterile for clinical use [21,22]. Solakoglu et al recently reported significant differences between two similar types of granular allografts, comprising Maxgraft granules, in augmenting and maintaining alveolar dimensions as part of a two-staged single implant restorative procedure while failing to show differences as part of an earlier human immunohistochemical and histometric study [6,23]. This controversy emphasizes the limited comparability between individual allografts and suggests a requirement for the material-and type-specific characterization and clinical performance validation of individual allografts.…”
Section: Introductionmentioning
confidence: 99%